2011
DOI: 10.1093/infdis/jir216
|View full text |Cite
|
Sign up to set email alerts
|

Measles and Rubella Elimination Initiatives in the Americas: Lessons Learned and Best Practices

Abstract: Countries in the World Health Organization Region of the Americas successfully interrupted endemic measles virus transmission 8 years after setting a regional measles elimination goal and have sustained this achievement since 2002. The vast experience from the region clearly demonstrates that measles elimination can be accomplished and maintained over time. This brief report summarizes the lessons learned and the best practices that evolved in the Americas during 3 measles elimination phases (ie, preeliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 9 publications
0
18
1
2
Order By: Relevance
“…Analysis of notification data indicates that Bavaria was hit by a major measles outbreak every two–three years between 2001 and 2013 27 , 28 . The absence of characteristically prolonged interepidemic spacing intervals suggests that Bavaria has probably not yet reached a pre-elimination phase 29 . In contrast, we found that measles incidence in the western area followed a constantly decreasing trend between 2007 and 2011.…”
Section: Discussioncontrasting
confidence: 55%
“…Analysis of notification data indicates that Bavaria was hit by a major measles outbreak every two–three years between 2001 and 2013 27 , 28 . The absence of characteristically prolonged interepidemic spacing intervals suggests that Bavaria has probably not yet reached a pre-elimination phase 29 . In contrast, we found that measles incidence in the western area followed a constantly decreasing trend between 2007 and 2011.…”
Section: Discussioncontrasting
confidence: 55%
“…Immunization coverage in the Mesoamerican region is generally high, but this study highlights the importance of studying not only coverage, but also effective coverage [Santos, ]. While studies of population measles serology in Mesoamerica have existed for more than 40 years [Golubjatnikov et al, ; Golubjatnikov et al, ], and while the importance of serosurveys in tracking progress toward elimination is well‐established [Castillo‐Solorzano et al, , ], there has been little expansion or incorporation of serosurveys in routine monitoring. The procedures described herein can be incorporated into existing data collection protocols in resource‐limited settings to monitor measles exposures, herd immunity, and effectiveness of immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the large burden of disease among young adults, which we see in this study, suggests that an SIA targeting adults aged 20-40 years could be useful. Previous research on measles elimination in the Americas has shown that SIAs for adults have been important in closing immunity gaps and moving towards elimination [29]. Moreover, given that the WHO WPR has also adopted a resolution for members to accelerate control of rubella, combining measles and rubella vaccines in SIAs for adults and other age groups would be a cost-effective mechanism to regionally eliminate both diseases [30].…”
Section: Discussionmentioning
confidence: 99%